Assessment of the Reliability and Validity of the Alberta Infant Motor Scale and Peabody Development Motor Scale in Highrisk Infants - Alhafdhi, Nour; AlOtaiby, Shahad (Malaysian Journal of Medicine and Health Sciences, 2022)
Introduction: The aim of this study was to investigate the correlation between Alberta Infant Motor Scale (AIMS) scores at 8 months and Peabody Developmental Motor Scale-2 (PDMS-2) and Peabody Developmental Gross Motor Scale-2 (PDMS-GM-2) scores at 18 months and 3 years in high-risk infants. Methods: This retrospective study included 105 high-risk infants at a Saudi Arabian tertiary care facility. Pearson correlation analysis was used for comparing scores. Additional subgroup analyses were performed for participants diagnosed with cerebral palsy at 18 months and for those who received physiotherapy. Result: AIMS scores at 18 months showed stronger correlations with PDMS-GM-2 scores than with PDMS-2 total scores, while these correlations decreased at 3 years. For the cerebral palsy subgroup, correlation with PDMS-2 scores at 18 months was relatively stronger than at 3 years. For the physiotherapy intervention subgroup, correlations with PDMS-GM-2 scores PDMS-2 total scores were similar at 18 months and 3 years. Conclusion: The AIMS predictive validity was lowest at 3 years in high-risk infants. A correlation was higher in participants with physiotherapy intervention and highest in participants with cerebral palsy. Outcome measures and treatment results should be cautiously reported during the first 3 years to prevent over-treating high-risk infants and decrease rehabilitation costs.